IMPLEMENTASI METODE PEMBELAJARAN DIFERENSIAL PADA MATA PELAJARAN PENDIDIKAN AGAMA ISLAM DALAM MENINGKATKAN MINAT BELAJAR SISWA DI SEKOLAH MENENGAH ATAS ADHYAKSA 1 KOTA JAMBI - Muhamad Arif Anwar; Minnah Elwiddah; Jamrizal (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aims to analyze the implementation of differentiated learning methods in Islamic Religious Education subjects to improve students’ learning interest at Adhyaksa 1 Senior High School, Jambi City. The research was conducted based on the phenomenon that differentiated learning had not been optimally implemented, resulting in students showing low enthusiasm and limited participation in the learning process. The objective of this study is to identify the implementation process, supporting and inhibiting factors, and the impact of differentiated learning on students’ learning interest. This study employed a qualitative descriptive approach. Data were collected through observation, interviews, and documentation involving teachers and students at Adhyaksa 1 Senior High School, Jambi City. The findings revealed that differentiated learning could increase students’ learning interest through varied learning models, diagnostic assessments, group-based learning activities, and presentations adjusted to students’ learning styles and interests. Supporting factors included adequate learning facilities, teacher professionalism, and the use of technology-based media such as projectors and gadgets. Meanwhile, inhibiting factors consisted of limited facilities, monotonous teaching methods, students’ lack of understanding of differentiated learning, and teachers’ limited technological competence. Therefore, the implementation of differentiated learning contributes positively to creating a more active, engaging, and student-centered learning environment in Islamic Religious Education classes.